Genetic diversity and molecular phylogeny of Anaplasma marginale studied longitudinally under natural transmission conditions in Rio de Janeiro, Brazil - Silva, Jenevaldo Barbosa [UNESP]; Goncalves, Luiz Ricardo [UNESP]; Varani, Alessandro de Mello [UNESP]; Andre, Marcos Rogerio [UNESP]; Machado, Rosangela Zacarias [UNESP] (Elsevier B.V., 2015)
Anaplasma marginale is the most prevalent tick-borne pathogen in cattle in tropical and subtropical regions of the world. Major Surface Protein 1a (MSP1a) has been found to be a stable genetic marker for identifying A. marginale isolates within geographical regions. It is conserved in cattle during infection and tick-borne transmission of the pathogen. The aim of the present longitudinal study was to determine occurrences of genetic diversity associated with high prevalence of A. marginale under natural transmission conditions. Twenty calves were evaluated every 3 months during the first year of life. Rickettsemia levels due to A. marginale, measured as the number of msp1 alpha copies in the blood of positive calves, ranged from 2.06 x 10(3) to 4.36 x 10(12). The numbers of MSP1a tandem repeats among MSP1a tandem repeats were 3 and 6. The predominant msp1 alpha microsatellite was E, and another MSP1a tandem repeat was found that presented genotype G. Nineteen different MSP1a tandem repeats of A. marginate were found circulating in animals. The MSP1a tandem repeats 4-63-27 (27.5%), 78-24(2)-25-31 (n = 21.6%) and tau-10(2)-15 (n=17.6%) were the ones most commonly observed. Twenty-two MSP1a tandem repeats resulted in new sequences with amino acid changes, as shown in this study. Thirty sequences were found for the first time in Brazil. Glycine, glutamate, serine and alanine amino acids were found at position 20. During the study, 80% (16/20) of the animals were infected by more than one genotype. Three animals were born infected, with MSP1a tandem repeats 4-63-27, 78-24(2)-25-31 and tau-10(2)-15, thus indicating occurrence of transplacental transmission. In the phylogenetic analysis, 19 different MSP1a tandem repeats of A. marginate were found in the cattle, which suggested that many MSPla tandem repeats and high variation in MSP1a were occurring.
Keywords: Brazil; Cattle; Genotype; MSP1a; Tandem repeats